Hardware-in-the-loop controller testing and visualization of an industrial gantry - Leao Moreira, M.; Singh, R.; Gomez-Badillo, A.; Albakri, B.; Venugopal, V.; Park, Y.; Cetin, S. (Frontiers in Mechanical Engineering, 2025)
In factory automation applications, the embedded control system components are often available as off-the-shelf products, while the mechanical components and environment in which they will work are still under development. Thus, the need arises to test control systems without the final assembly. This paper introduces a hardware-in-the-loop (HIL) virtual environment for control system testing, design planning, and operator training. Controller hardware and software are configured as in the actual application, whereas electro-mechanical components are virtually constructed using Unreal Engine 5 and Matlab Simulink. Motion data from the model can be used to optimize the actuator controller, make physical design assessments, and predict possible failure scenarios such as software/hardware malfunctions. The environment is used to validate an industrial gantry robot’s control systems and structural design. The testing is successful in using real-time controller inputs to generate visual display and physical assessments of the robot’s design. Similar techniques can be applied to simulate different robot configurations using Codesys and Unreal Engine 5 or similar programs.